2014
DOI: 10.3109/13625187.2014.944639
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health and HIV in border districts affected by migration and poverty in Tanzania

Abstract: Objectives To assess HIV knowledge, attitudes, sexual practices and sexual and reproductive health (SRH) service delivery in border areas of Tanzania, with a view to support the prioritisation of SRH interventions in border areas. MethodsThe target sample comprised randomly selected people living near the border, aged 15-49. To gather information, we utilised: (i) a standardised questionnaire (n=86; 42 men and 44 women) previously used in national household surveys conducted by the Tanzanian government;(ii) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Evidence in different countries highlights the complexity of HIV-related issues in this setting. For instance, a study in the border area of Tanzania found that migration attributed to the high rates of unsafe sex practice, while a study in the cross-border of Mexico-the United States of America (USA) shows that opioid drug practice was common among people residing in this setting [13, 15]. Another study among female sex workers on the border between Brazil and French Guiana indicated a low rate of HIV/AIDS testing uptake due to a lack of proper services [16].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence in different countries highlights the complexity of HIV-related issues in this setting. For instance, a study in the border area of Tanzania found that migration attributed to the high rates of unsafe sex practice, while a study in the cross-border of Mexico-the United States of America (USA) shows that opioid drug practice was common among people residing in this setting [13, 15]. Another study among female sex workers on the border between Brazil and French Guiana indicated a low rate of HIV/AIDS testing uptake due to a lack of proper services [16].…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of some hot-spots was that most of them were found on the cross-borders of Cameroon with CAR (Mbere, Lom et Djerem, Kadey, Boumba et Ngoko) and Congo (Haut-Nyong, Océan, Dja et Lobo and Mvila) respectively. Some studies revealed that border areas are generally subjected to a high rate of unsafe sex practice and a low level of HIV-related knowledge, attitudes, and practices [ 24 26 ]. This may explain the high risk of HIV infection in these subdivisions on the borders where there is high human mobility in and out.…”
Section: Discussionmentioning
confidence: 99%
“…Another characteristic of cluster 1 was that most of its subdivisions were found on the cross-borders of Cameroon with CAR(Mbere, Lom et Djerem, Kadey, Boumba et Ngoko) and Congo(Haut-Nyong, Dja et Lobo and Mvila) respectively. Some studies revealed that borders areas are generally subjected to a high rate of unsafe sex practice and a low level of HIV-related knowledge, attitudes, and practices [19,20,21]. This may explain the high risk of HIV infection in these subdivisions on the borders where there is high human mobility in and out.…”
Section: Discussionmentioning
confidence: 99%